Stoned—A Syndrome of D‐Lactic Acidosis and Urolithiasis. (23rd March 2018) - Berman, Casey M.; Merritt, Russell J.
Abstract: Short bowel syndrome (SBS) can lead to many complications related to the condition and its therapy. We describe 2 children with SBS who we believe are the second and third patients documented to have experienced both D‐lactic acidosis and urolithiasis. We review aspects of these SBS complications and recent findings on the microbiome of patients with SBS that may predispose to these complications.